Multi-criteria analysis of five reinforcement options for Peruvian confined masonry walls - Tarque N. (2019)
In Peru, construction of dwellings using confined masonry walls (CM) has a high percentage of acceptance within many sectors of the population. It is estimated that only in Lima, 80% of the constructions use CM and at least 70% of these are informal constructions. This mean that they are built without proper technical advice and generally have a high seismic vulnerability. One way to reduce this vulnerability is by reinforcing the walls. However, despite the existence of some reinforcement methods in the market, not all of them can be applied massively because there are other parameters to take into account, as economical, criteria for seismic improvement, reinforcement ratio, etc. Therefore, in this paper the feasibility of using five reinforcement techniques has been studied and compared. These reinforcements are: welded mesh (WM), glass fiber reinforced polymer (GFRP), carbon fiber reinforced polymer (CFRP), steel bar wire mesh (CSM), steel reinforced grout (SRG). The Multi-Criteria Decision Making (MCDM) method can be useful to evaluate the most optimal strengthening technique for a fast, effective and massive use plan in Peru. The results of using MCDM with 10 criteria indicate that the Carbon Fiber Reinforced Polymer (CFRP) and Steel Reinforced Grout (SRG) methods are the most suitable for a massive reinforcement application in Lima.